2019
DOI: 10.1038/s41598-019-38562-2
|View full text |Cite
|
Sign up to set email alerts
|

Ocean variability and air-sea fluxes produced by atmospheric rivers

Abstract: Atmospheric rivers (ARs) cause heavy precipitation and flooding in the coastal areas of many mid-latitude continents, and thus the atmospheric processes associated with the AR have been intensively studied in recent years. However, AR-associated ocean variability and air-sea fluxes have received little attention because of the lack of high-resolution ocean data until recently. Here we demonstrate that typical ARs can generate strong upper ocean response and substantial air-sea fluxes using a high-resolution (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 31 publications
4
41
1
Order By: Relevance
“…As discussed above, these large waves were the main responsible for augmenting the sea level in both the short-and long-period bands. Although a few studies have reported relations between ARs and high water levels in continental coastlines (Khouakhi and Villarini 2016;Shinoda et al 2019) via wind setup, what we report here is somewhat different because the phenomena occur on a steep volcanic island surrounded by deep waters where the mechanism is wave setup rather than wind setup. Many issues regarding the connection between ARs and extreme sea levels at Rapa Nui are still unclear for us, but their scientific and societal importance revealed by the observations presented herein motivates their investigation.…”
Section: The Role Of Atmospheric Riverscontrasting
confidence: 65%
“…As discussed above, these large waves were the main responsible for augmenting the sea level in both the short-and long-period bands. Although a few studies have reported relations between ARs and high water levels in continental coastlines (Khouakhi and Villarini 2016;Shinoda et al 2019) via wind setup, what we report here is somewhat different because the phenomena occur on a steep volcanic island surrounded by deep waters where the mechanism is wave setup rather than wind setup. Many issues regarding the connection between ARs and extreme sea levels at Rapa Nui are still unclear for us, but their scientific and societal importance revealed by the observations presented herein motivates their investigation.…”
Section: The Role Of Atmospheric Riverscontrasting
confidence: 65%
“…This HYCOM re-analysis data have been intensively validated 50 and used [51][52][53][54] in several contexts during the past ten years. The global HYCOM re-analysis uses the Navy Coupled Ocean Data Assimilation (NCODA) system 55,56 for data assimilation.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of intensity and duration of irradiation on themal energy storage in water was stated by Wang et al (2019). Furthermore, thermal energy storage in water determines the thermal flux from water to air (Sarbu and Sebarchievici, 2018;Shinoda et al, 2019).…”
Section: Discussionmentioning
confidence: 99%